Auditor Experience and Audit Quality on Auditor Performance with Professional Ethics as a Moderating Variable in Public Accounting Firms in DKI Jakarta, Surabaya, and Semarang - Zakkiandri; Karsam (GoAcademica Research & Publishing, 2024)
This research identifies and determines the relationship between Auditor Experience, Audit Quality, and Auditor Performance in Public Accounting Firms in DKI Jakarta, Surabaya, and Semarang. Professional Ethics acts as a moderating variable. Quantitative method with a sample of 12 Public Accounting Firms (300 respondents) using purposive sampling. Data analysis uses Multivariate Structural Equation Model (SEM) SmartPLS 3 with a focus on outer model and inner model analysis. The results of this study show that partially, auditor experience has a significant effect on auditor performance (P = 0.000 < 0.05), while audit quality has no significant effect (P = 0.311 > 0.05). Professional ethics as a moderating variable influences audit performance (P = 0.024 < 0.05). However, auditor experience which is moderated by professional ethics, and audit quality which is moderated by professional ethics do not have a significant effect (P = 0.824 and P = 0.242 < 0.05). Simultaneously, auditor performance is influenced by auditor experience and audit quality by 90% (R2 = 0.901).